Adaptive cycle and outcome response of farmers’ livelihoods under the background of rural transformation: a case study from the arid northwest region of China - Sha Yin; Xinjun Yang; Jia Chen (International Journal of Agricultural Sustainability)
Rural transformation is important to deal with environmental change. In the context of rural transformation, institutional and policy changes have a great impact on farmers’ livelihoods. The adaptive cycle and the outcomes of farmers’ livelihoods reflect the impacts of rural transformation on farmers. In this study, we constructed a new analytical framework to analyse the adaptive cycle of farmers’ livelihoods and established an indicator system to quantify the adaptive cycle. Meanwhile, we identified the factors influencing the adaptive cycle of farmers’ livelihoods. We showed that farmers’ livelihood in Minqin County, Gansu Province, Northwest China, from 1990 to 2017 had gone through the phases of Reorganization (α), Reorganization (α)→Exploitation (r), and Exploitation (r). The sources of farmers’ livelihoods were gradually diversified and the per capita net income had gradually increased. The reform of the socialist market economy and the ecological governance policies were the fundamental factors influencing the change of potential and resilience in the adaptive cycle. Resilience was the most important factor affecting the outcome of farmers’ livelihoods. These findings can provide references to adjust government strategies and the choice of farmers’ livelihoods, which is helpful in achieving sustainable livelihoods, rural transformation, and development in arid areas.